Analisis Kedudukan Perempuan dalam Hukum Keluarga Islam Perspektif Tafsir Surat An-Nisa Ayat 34 dan Teori Feminisme - Sridepi Sridepi; Adnan Azzaki; Khairunnas Rajab; Khairunnas Jamal; Almi Jera (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
The issue of women's status in Islamic family law has remained a subject of ongoing debate, particularly when examined through the interpretation of Surah An-Nisa verse 34, which designates men as leaders (qawwam) within the family. This study aims to analyze the verse using an interdisciplinary approach that integrates classical and contemporary Qur’anic exegesis with feminist theory. This approach not only explores the dynamics of interpretation from traditional scholars such as al-Tabari and Ibn Kathir to modern thinkers like Amina Wadud, but also critically examines how various strands of feminism—liberal, radical, and Islamic—provide analytical frameworks to challenge patriarchal structures in Islamic family law. This research employs a qualitative method through library research, supported by normative and juridical-historical approaches. The findings reveal that Surah An-Nisa verse 34 can be understood in a more egalitarian manner when interpreted in light of evolving social contexts, without disregarding the fundamental principles of Sharia. The study concludes that integrating Qur’anic interpretation with feminist perspectives offers the potential for a more just, inclusive, and contextually responsive understanding of Islamic family law in addressing gender equality in contemporary society.